Ceria nanocrystals decorated mesoporous silica nanoparticle based ROS-scavenging tissue adhesive for highly efficient regenerative wound healing. (January 2018) - Wu, Haibin; Li, Fangyuan; Wang, Shuaifei; Lu, Jingxiong; Li, Jinquan; Du, Yang; Sun, Xiaolian; Chen, Xiaoyuan; Gao, Jianqing; Ling, Daishun
Abstract: Restoration of tissue integrity and tissue function of wounded skin are both essential for wound repair and regeneration, while synergistic promotion of the two remains elusive. Since elevated reactive oxygen species (ROS) production in the injured site has been implicated in triggering a set of deleterious effects such as cellular senescence, fibrotic scarring, and inflammation, it is speculated that alleviating oxidative stress in the microenvironment of injured site would be beneficial to promote regenerative wound healing. In this study, a highly versatile ROS-scavenging tissue adhesive nanocomposite is synthesized by immobilizing ultrasmall ceria nanocrystals onto the surface of uniform mesoporous silica nanoparticles (MSN). The ceria nanocrystals decorated MSN (MSN-Ceria) not only has strong tissue adhesion strength, but also significantly restricts ROS exacerbation mediated deleterious effects, which efficiently accelerates the wound healing process, and more importantly, the wound area exhibits an unexpected regenerative healing characteristic featured by marked skin appendage morphogenesis and limited scar formation. This strategy can also be adapted to other wound repair where both ROS-scavenging activity and tissue adhesive ability matter. Graphical abstract: Regenerative Wound Healing! Efficient restoration of tissue integrity and function are achieved by using a ROS-scavenging tissue adhesive MSN-Ceria. The synergistic effect between nanobridging effect for restoration of tissue integrity and ROS scavenging for oxidative stress modulating enable not only accelerated wound healing process but also an unexpected regenerative healing.